Prometna problematika istočne Hrvatske - Božičević, Josip (Promet - Traffic&Transportation, 2012)
This paper deals with the issues of road, railway, river and postal traffic in East Croatia. Its Introduction section makes a review of the pre-war condition of traffic infrastructure facilities in the national region of East Croatia, as making part of the European integration processes, while being at the same time significant for the Republic of Croatia in the service of development of the entire national region. The paper further discusses damages from wartime devastation and their adverse impacts as felt in discrupture of traffic flows. The author elaborates and gives recommendations on the course of actions on the reconstruction as needed for prompt operation of the traffic system, in conjunction with the programs of construction and development of traffic infrastructure facilities in the post-war period.